Differences in the response in the dermis of the tails of young and old SD rats to treatment with bipolar RF. (11th January 2021) - Beltrán‐Frutos, E.; Ferrer, C.; Seco‐Rovira, V.; Martínez‐Hernández, J.; Serrano‐Sánchez, M. I.; Pastor, L. M.
Abstract: Background: The passing of the years is marked by intrinsic (chronological) and extrinsic aging, caused by photoaging, which is characterized by a decrease in collagen and the deposition of abnormal elastic fibers in the dermis. The use of bipolar radiofrequency (RF) increases fibroblast proliferation and differentiation, accompanied by collagen synthesis and a subsequent increase in connective tissue, and it is not known whether the biological effects of this type of radiofrequency on the dermis are similar regardless of the age of the individual or whether such effects are altered by the aging process itself. Aims: The objective was to perform a histological study of the changes in the tail dermis of young and old rats after submitting them to bipolar RF, to determine cell proliferation and volume of connective tissue. Methods: One part of the rat tail was fixed in formol and processed for light microscopy and another part processed for electron microscopy. Results: The number of fibroblasts/unit area and cells positive to nuclear proliferation antigen was higher in young animals. Significant differences were observed regarding expression of HSP‐47 protein, and the value was always lower in old rats. No significant differences were observed in the percentage of connective tissue. No histological alterations were observed in any rats. Conclusion: Treatment with RF increased the number of fibroblasts located in the connective tissue of the young rats. In addition, the effect of a single treatment on the population of fibroblasts in young animals was sufficient to activate the synthesis of new collagen.